Eco-Pesantren-Based Islamic Education Management - Hermawansyah, Hermawansyah (Fitrah, 2025)
The concept of eco-pesantren, or environment-based Islamic education management, is an innovative educational model that integrates Islamic values with environmental sustainability principles within Islamic boarding schools. This study aims to analyze the challenges and strategic approaches to implementing eco-pesantren in a holistic and sustainable manner. Despite its relevance, the implementation of eco-pesantren faces various obstacles, such as low environmental awareness, limited institutional resources, and entrenched habits that are not eco-friendly. Using a qualitative-descriptive method, this research explores the integration of environmental values into curriculum development, institutional culture, facility management, and daily practices. The study also emphasizes the role of Islamic theological foundations, leadership, and community engagement in supporting eco-pesantren initiatives. Findings reveal that effective implementation requires consistent environmental education, curriculum integration, role-modeling by educators, and partnerships with external stakeholders. Ultimately, this study contributes to the discourse on sustainable Islamic education and proposes eco-pesantren as a strategic model for nurturing environmentally conscious, spiritually grounded, and socially responsible generations.